(untitled) (MedS Alliance Journal of Medicine and Medical Sciences, 2022)
INTRODUCTION: Attention deficit hyperactivity disorder (ADHD) is a neuro-developmental disorder that typically first manifest early in childhood and often persist into adulthood which can affect the academic achievement, well-being and social interactions of children. The objective of this study was to assess knowledge about ADHD among the government school teacher and to find the association between ADHD knowledge with their demographic variables. MATERIALS AND METHODS: A cross section descriptive research design was adopted. A total of 112 numbers of samples were selected from government schools of Janakpurdham, Nepal by use of purposive sampling. The information was collected through the use of the Knowledge Attention Deficit Disorder Scale (KADDS) tool, and subsequently, data were analyzed using Statistical Package for Social Sciences (SPSS). RESULTS: The result revealed that 43.8% demonstrated insufficient knowledge, while only 56.2% possessed adequate knowledge. There was significant association of gender and the ADHD knowledge among the government school teachers (p = 0.016). CONCLUSIONS: Insufficient knowledge about ADHD was noted among school teachers, indicating a need for the government to provide targeted training and in-service education in this field.